Epidemiology, Prognosis, and Evolution of Management of Septic Shock in a French Intensive Care Unit: A Five Years Survey - Nicolas Boussekey; Juliette Cantrel; Lise Dorchin Debrabant; Joachim Langlois; Patick Devos; Agnes Meybeck; Arnaud Chiche; Hugues Georges; Olivier Leroy (Critical Care Research and Practice)
Purpose. To evaluate the epidemiology, prognosis, and management of septic shock patients hospitalized in our intensive care unit (ICU). Materiel and Methods. Five-year monocenter observational study including 320 patients. Results. ICU mortality was 54.4%. Independent mortality risk factors were mechanical ventilation (OR=4.97), Simplify Acute Physiology Score (SAPS) II > 60 (OR=4.28), chronic alcoholism (OR=3.38), age >65 years (OR=2.65), prothrombin ratio <40% (OR=2.37), and PaO2/FiO2 ratio <150 (OR=1.91). These six mortality risk factors recovered allow screening immediately septic shock patients with a high mortality risk. Morbidity improved with time (diminution of septic shock complications, increase of the number of days alive free from mechanical ventilation and vasopressors on day 28), concomitant to an evolution of the management (earlier institution of all replacement and medical therapies and more initial volume expansion). There was no difference in mortality. Conclusion. Our study confirms a high mortality rate in septic shock patients despite a new approach of treatment.